2014
DOI: 10.1182/blood-2013-09-527853
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged lymphocytosis during ibrutinib therapy is associated with distinct molecular characteristics and does not indicate a suboptimal response to therapy

Abstract: Key Points Persistent CLL cells during ibrutinib therapy show evidence of biochemical activation, but inhibited BCR and no proliferation. Long lymphocytosis during ibrutinib therapy is not associated with adverse progression-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
205
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(232 citation statements)
references
References 24 publications
22
205
1
4
Order By: Relevance
“…A recent analysis from the phase 2 trial of single-agent ibrutinib in patients with relapsed/refractory CLL showed that PR with prolonged lymphocytosis was not associated with inferior PFS outcomes compared with a traditional clinical response. 32 This finding with single-agent ibrutinib 32 along with data from the present study with the combination of ibrutinib and ofatumumab and reported attenuation of lymphocytosis with the combination of ibrutinib and rituximab 36 raises an important question on whether additional targeting of lymphocytosis with anti-CD20 monoclonal antibodies improves long-term PFS/overall survival outcomes over single-agent ibrutinib therapy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…A recent analysis from the phase 2 trial of single-agent ibrutinib in patients with relapsed/refractory CLL showed that PR with prolonged lymphocytosis was not associated with inferior PFS outcomes compared with a traditional clinical response. 32 This finding with single-agent ibrutinib 32 along with data from the present study with the combination of ibrutinib and ofatumumab and reported attenuation of lymphocytosis with the combination of ibrutinib and rituximab 36 raises an important question on whether additional targeting of lymphocytosis with anti-CD20 monoclonal antibodies improves long-term PFS/overall survival outcomes over single-agent ibrutinib therapy.…”
Section: Discussionmentioning
confidence: 72%
“…[24][25][26] Ofatumumab is approved in the United States for treatment of CLL refractory to fludarabine and alemtuzumab 27 and in combination with chlorambucil for previously untreated CLL where fludarabine-based treatment is inappropriate. 28,29 Studies with single-agent ibrutinib showed early lymphocytosis in patients with CLL, [30][31][32] which is considered a pharmacodynamic effect of ibrutinib resulting in mobilization of lymphocytes into the peripheral blood from tissue compartments. 18,20 Combining ibrutinib with an anti-CD20 monoclonal antibody to clear blood lymphocytes was thought to reduce the duration and incidence of lymphocytosis, thereby potentially shortening the time to response.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance mutations were detected when progressive disease was first observed, but not before treatment or during the initial response to treatment (including lymphocytosis) (14,15). In addition, the CLL cells found during lymphocytosis in nonprogressing patients have been found to be quiescent rather than carrying mutations that confer ibrutinib resistance (30,31).…”
Section: Resistant Mutants Can Have a Selective Advantage In The Absementioning
confidence: 99%
“…This phenomenon is due to rapid (<24 hr after drug intake) egress [110] and mobilization of lymphocytes residing in the protective tissue niches of lymph nodes into the peripheral blood [111,112]. These agents interfere with the adhesion molecules, chemokine receptor interactions and homing of CLL cells [113,114].…”
Section: Bcr Signaling Kinase Inhibitorsmentioning
confidence: 99%